Simulaciones por dinámica molecular para el estudio de propiedades biofísicas de estafiloxantina en membranas modelo de DMPG y DPPG (2020)
Staphylococcus aureus is a clinically important pathogen that has received public attention due to the development of antibiotic resistance. Furthermore, drug resistance could be due to the modulation of mechanical properties of the plasma membrane of bacteria. One of the main compounds of the S. aureus membrane is staphyloxanthin, which increases in concentration when bacteria is subjected to stress and it is speculated that it increases the rigidity of the plasma membrane of the bacteria. However, there is a gap in the knowledge of the biophysical properties affected by the presence of staphyloxanthin. Due to this gap, the effect of presence of staphyloxanthine (STX) in systems with model lipids DMPG and DPPG, at a temperature of 323K is studied using molecular dynamics simulations. Staphyloxanthin is inserted into model membranes at the following concentrations: 1STX: 128DMPG, 1STX: 128DPPG, 15% mol STX in DMPG and 15% mol STX in DPPG...